Republic of Armenia : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion; Staff Report; and Press Release on the Executive Board Consideration. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Fourth Review Under the Poverty Reduction and Growth Facility for Armenia. Armenia's economy performs strongly. All end-December 2006 quantitative and all but one structural performance criteria were observed. The main policy challenges are to broaden economic growth, raise tax revenues, and manage large foreign exchange inflows. Fiscal policy remains appropriate. Meeting the ambitious 2007 revenue target will require broadening the tax base and strengthening administration. The stance of monetary policy is appropriate.